Epidemiological analysis of stroke patients with emphasis on access to acute-phase therapies - Camila Favoreto do ROSÁRIO; Walker Garcia FERNANDES NETO; André Luiz PESSOTTI; Beatriz Cardoso RODRIGUES; Juliana Diniz BAPTISTA; Marcela SEGATTO; Vinicius Santana NUNES; Leandro de Assis BARBOSA; Abraão Ferraz Alves PEREIRA; Christiane Lourenço MOTA; José Antônio FIOROT JÚNIOR (Arquivos de Neuro-Psiquiatria)
ABSTRACT Background: Stroke is a public health problem. For patients with ischemic stroke, venous thrombolysis and mechanical thrombectomy are effective therapeutic options. However, even after the National Stroke Treatment Guidelines were published in 2012, the number of cases treated is still lower than expected. Objective: To identify the determining factors for obtaining access to acute-phase therapies in the state of Espírito Santo (ES) and investigate the profile of stroke patients treated at the Central State Hospital (HEC). Methods: Retrospective data from the medical records of 1078 patients from May 2018 to December 2019 were analyzed. Results: Among the 1,078 patients, 54.9% were men and the most prevalent age group was 60 to 79 years. Systemic arterial hypertension was the main single risk factor. Regarding treatment modality among the patients who arrived at the HEC within the therapeutic window, 47% received some type of acute-phase therapy. Waking up with the deficit was the main contraindication for venous thrombolysis in these cases. Conclusions: Application of the flowchart established by SESA-ES seemed to be effective for enabling responsiveness of care for stroke victims. Public emergency transport services had a fundamental role in this process. In addition, the care provided by the tertiary stroke center provided excellent access to acute-phase therapies. However, despite the efficiency of the service provided at the HEC, it only reached a maximum of 50% of the ES population. This service model therefore needs to be expanded throughout the state.